1994
DOI: 10.1016/0035-9203(94)90176-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of iron supplementation during pregnancy, given by traditional birth attendants, on the prevalence of anaemia and malaria

Abstract: A randomized, double-blind, placebo-controlled community-based trial of oral iron supplementation (200 mg ferrous sulphate daily) administered to multigravid pregnant women by traditional birth attendants (TBAs) was carried out in a rural area of The Gambia. Iron supplementation led to a significant reduction in the prevalence of anaemia and of iron deficiency. Iron supplementation was not accompanied by increased susceptibility to malaria infection; there was no difference in the prevalence and severity of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 13 publications
6
79
0
2
Order By: Relevance
“…41,42 Iron supplementation during pregnancy is therefore generally recommended and has been shown to increase the haemos s globin level and PCV in the mother's blood postsdelivery and to increase the mean birth weight of infants. 43 Maternal anaemia was not prevented in our study and this may relate to poor adherence to treatment with iron supplements or failure to control malaria adequately because of chloroquine resistance.…”
Section: Discussionmentioning
confidence: 63%
“…41,42 Iron supplementation during pregnancy is therefore generally recommended and has been shown to increase the haemos s globin level and PCV in the mother's blood postsdelivery and to increase the mean birth weight of infants. 43 Maternal anaemia was not prevented in our study and this may relate to poor adherence to treatment with iron supplements or failure to control malaria adequately because of chloroquine resistance.…”
Section: Discussionmentioning
confidence: 63%
“…There are insufficient data from developing countries to draw conclusions; the few RCTs are inconclusive because of small sample size, problems with compliance, and large losses to follow-up. Small trials in The Gambia, Nigeria, and India showed no significant effects on birth weight, 140,[153][154][155] although 1 large trial in Niger showed a significant increase in birth length and Apgar scores and a reduction in PMR. 156 There are several other reports of iron therapy in pregnancy from developing countries that are relatively less stringent in their inclusion and exclusion criteria.…”
Section: Iron Supplementationmentioning
confidence: 99%
“…Thus, maternal iron stores are associated with earlier development of anemia during infancy, frequently around 4 months of age. 7,8 Published local surveys assessing the prevalence of anemia in children less than 12 years of age in Mexico were recently reviewed. 9 In this review the highest prevalence of anemia was found in children under 3 years of age, living in Mexico City (42.7 % for anemia, and 57% for iron deficiency), 10 and in children of low socioeconomic status aged 18 to 36 months, living in rural areas of the center plateau of Mexico (70% for anemia and 48% for iron deficiency).…”
Section: Introductionmentioning
confidence: 99%